PERINTAH PEJABAT TATA USAHA NEGARA MELALUI TELEPON DAN AKIBAT HUKUMNYA - Muchamad Arif Agung Nugroho (Qistie Jurnal Ilmu Hukum, 2012)
Orders over  the phone about a moratorium on corruption by Wamenkumham remission is an interesting thing to be appointed to the writing of the law, because such events have been detrimental to the interests of the convicted of corruption. Countries such as not having  the means  to resolve  the dispute. Therefore,  this paper is to review the legal argumerntasi against the order along with its legal effect. When viewed from the state administrative law and procedural law state administrative courts,  then  the command can be equated with  legal decisions, so  it could be the subject of dispute that can be sued in state administrative courts. In addition,  the command also meet  the criteria  for maladministration  to be reported to the Ombudsman of the Republic of Indonesia and the recommendations issued by  the  issuing  sanctions against  the officials.Key words: administrative official orders, due  to  legal, ombudsman